(untitled) (AYUSHDHARA, 2025)
The sixth chapter of the Sushruta Samhita Sutra Sthana is the Ritucharya Adhyaya. Acharya Sushruta clarified that Roga can be avoided before it manifests if one abides by Ritucharya’s precepts. Thus, Ritucharya is an Ayurvedic preventive and health-promoting practice that helps people live in harmony with nature and stay healthy throughout time. Sushruta Samhita Sutra Sthana is the source of literature about Ritucharya. In Ritucharya, Acharya Sushruta explains what should be done in each season (Samshodhana kala) to stop illnesses before they start According to him, for Swasthya Rakshana Snehapana and Basti should be conducted in Varsha Ritu to calm Vata dosha, Virechana should be performed in Sharad Ritu to balance Pitta dosha, and Vamana should be performed in Vasanta Ritu to balance Kapha dosha.